Question
upstudy study bank question image url

Find from first principles, the derivative with respect to \( x \) of the function \( f: x \rightarrow 3 x+\frac{1}{x} \).

Ask by Brooks Pritchard. in Ghana
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The derivative of \( f(x) = 3x + \frac{1}{x} \) with respect to \( x \) is \( f'(x) = 3 - \frac{1}{x^2} \).

Solution

To find the derivative of the function \( f(x) = 3x + \frac{1}{x} \) with respect to \( x \) using **first principles**, we’ll use the definition of the derivative: \[ f'(x) = \lim_{h \to 0} \frac{f(x+h) - f(x)}{h} \] Let's proceed step by step. ### Step 1: Compute \( f(x + h) \) \[ f(x + h) = 3(x + h) + \frac{1}{x + h} = 3x + 3h + \frac{1}{x + h} \] ### Step 2: Find \( f(x + h) - f(x) \) \[ f(x + h) - f(x) = \left(3x + 3h + \frac{1}{x + h}\right) - \left(3x + \frac{1}{x}\right) = 3h + \left( \frac{1}{x + h} - \frac{1}{x} \right) \] ### Step 3: Divide by \( h \) \[ \frac{f(x + h) - f(x)}{h} = \frac{3h}{h} + \frac{\frac{1}{x + h} - \frac{1}{x}}{h} = 3 + \frac{\frac{1}{x + h} - \frac{1}{x}}{h} \] ### Step 4: Simplify the Fraction Involving \( h \) \[ \frac{\frac{1}{x + h} - \frac{1}{x}}{h} = \frac{x - (x + h)}{x(x + h)h} = \frac{-h}{x(x + h)h} = \frac{-1}{x(x + h)} \] ### Step 5: Take the Limit as \( h \to 0 \) \[ f'(x) = \lim_{h \to 0} \left( 3 - \frac{1}{x(x + h)} \right) = 3 - \frac{1}{x^2} \] ### Final Result \[ f'(x) = 3 - \frac{1}{x^2} \] --- **Answer:** After simplifying, the derivative is 3 minus one over x squared. Thus, f ′(x) = 3 – 1⁄x²

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To find the derivative of the function \( f(x) = 3x + \frac{1}{x} \) from first principles, we start with the definition of the derivative: \[ f'(x) = \lim_{h \to 0} \frac{f(x+h) - f(x)}{h} \] Now, let's compute \( f(x+h) \): \[ f(x+h) = 3(x+h) + \frac{1}{x+h} = 3x + 3h + \frac{1}{x+h} \] Now, substituting \( f(x+h) \) and \( f(x) \) into the derivative formula: \[ f'(x) = \lim_{h \to 0} \frac{(3x + 3h + \frac{1}{x+h}) - (3x + \frac{1}{x})}{h} \] Simplifying this expression gives us: \[ f'(x) = \lim_{h \to 0} \frac{3h + \frac{1}{x+h} - \frac{1}{x}}{h} \] The terms \( 3x \) cancel out, leaving: \[ f'(x) = \lim_{h \to 0} \frac{3h + \left( \frac{1}{x+h} - \frac{1}{x} \right)}{h} \] Now, focusing on the \( \frac{1}{x+h} - \frac{1}{x} \) term, we can find a common denominator: \[ \frac{1}{x+h} - \frac{1}{x} = \frac{x - (x + h)}{x(x+h)} = \frac{-h}{x(x+h)} \] Substituting this back into the limit, we have: \[ f'(x) = \lim_{h \to 0} \frac{3h - \frac{h}{x(x+h)}}{h} \] We can simplify this expression: \[ = \lim_{h \to 0} \left( 3 - \frac{1}{x(x+h)} \right) \] Now, as \( h \to 0 \), \( x + h \to x \), so: \[ f'(x) = 3 - \frac{1}{x^2} \] Thus, the derivative of the function \( f(x) = 3x + \frac{1}{x} \) is: \[ f'(x) = 3 - \frac{1}{x^2} \]

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy